Ice Spheres as Model Snow: Tumbling, Sintering, and Mechanical Tests - Willibald, Carolin; Scheuber, Sophia; Löwe, Henning; Dual, Jürg; Schneebeli, Martin (Frontiers in Earth Science, 2019)
The snow microstructure is crucial for the mechanical behavior of snow, but is usually simplified in numerical models. In Discrete Element Models (DEM), often used in snow mechanics, the microstructure is typically represented by sphere assemblies. This renders a model validation difficult, as the real snow crystal shapes affect the actual contacts and consequently the macromechanical behavior. To approach this problem from the experimental side, we created simplified microstructures comprising spherical ice particles and examined this model snow under structural and mechanical aspects. We developed a new method to create uniform ice spheres and performed a detailed particle characterization using 3D computed tomography (CT). We examined sintered sphere assemblies to relate microstructural and macromechanical properties in a geometrically well-defined system. Microstructural variation was created by varying the sample density and sintering time, to study the role of the number and size of contacts. 3D CT scans were taken of sintered sphere samples, which were then tested in unconfined compression experiments together with a nature identical snow type as a reference. The scans were evaluated regarding the number of particles and contacts, and were used to compute the elastic modulus, as additional mechanical property. The results of the particle characterization showed the spherical shape and sharp size-distribution of the particles, which are the main prerequisites for model validation. The CT image analysis showed the reproducibility of the sphere assemblies and can be applied for efficient reconstruction of the experimental samples as initial condition for simulations. The mechanical properties conform with the reference snow and the expectations from literature, however, the CT scans revealed a complex geometry of the sintered contacts with measurable impact on the mechanical properties.